The seductive illusion of hard work. - Amitabh, Utkarsh (SAGE Publishing, 2020)
"People take great pride in flaunting their punishing work routines. The Seductive Illusion of Hard Work establishes that hard work is necessary but insufficient for success. In fact, misdirected hard work is way worse than no work at all. This book includes various real-life examples from the corporate world that has constantly exaggerated the role of hard work and underplayed the critical role of choices and mentorship in creating conditions for success. The young workforce is experiencing burnout and it is suspected that the romantic proclamations and obsession about hard work has lots to do with it. This book discusses all these issues and finally offers a solution-oriented approach to the myth about succeeding in work life"--